ANALISIS RASIO LIKUIDITAS DAN PROFITABILITAS UNTUK MENGUKUR KINERJA KEUANGAN PADA PT ASTRA INTERNATIONAL TBK PERIODE 2014-2023 - Fatika Sari, Dwi; Janudin (Journal of Research and Publication Innovation, 2024)
This research aims to determine the condition of the financial performance of the company PT Astra International Tbk in the period 2014 to 2023 using financial ratio measuring instruments. The research method used is a quantitative descriptive method. Meanwhile, the profitability ratio is the company's ability to generate profits during a certain period. From the results of research using the liquidity ratio from 2014-2023, looking at the current ratio, the results showed that 135.36% of the companies were declared healthy. The quick ratio obtained a result of 111.93% of the company being declared healthy. Judging from the cash ratio, the results were 38.26%. From the results of calculating profitability ratios using Net Profit Margin, the company was declared unhealthy because the average value was still below 12% according to the standards of the Minister of Finance Decree No. 740. Judging from the Return On Assets, the company was declared unhealthy. healthy because the average value is still below 12% according to the standard of Decree of the Minister of Finance No. 740. And seen from the Return On Equity, the result is 14.43%. The company is declared very healthy because the value is above the standard of Decree of the Minister of Finance No. 740. And seen from the Operational Profit Margin got a result of 13.98% and the company was declared very healthy because the average value was above 12% according to the Minister of Finance Decree No. 740. And seen from the Gross Profit Margin, it got a result of 21.27% and the company was declared very healthy because the average value was above 12 % according to the standards of Minister of Finance Decree No. 740.